The usefulness of feedback. (November 2021) - Henderson, Michael; Ryan, Tracii; Boud, David; Dawson, Phillip; Phillips, Michael; Molloy, Elizabeth; Mahoney, Paige
Feedback can occur before and after assessment submission, but needs to be useful in order for students to improve their subsequent performance. Arguably, undergraduate students, and particularly international, online and new students, are especially in need of feedback to effectively engage in academic and disciplinary expectations. Therefore, this article draws on survey data from students, disaggregated by mode of study, citizenship of enrolment and year of study, to explore their experiences of feedback usefulness both before and after assessment submission. Overall, undergraduate students were positive; however, this perception decreased according to their year level. Comparisons between online and international students also revealed key differences. A conclusion is that undergraduate students cannot be treated homogeneously, and educators need to attend to the feedback experiences of different student groups as they progress through their programme.